Sistem Informasi Monitoring Program Kerja pada Desa Gelumpang Pirak Menggunakan Metode Activity Based Budgeting - Ikbal Hakim; Suendri Suendri (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Gelumpang Pirak Village has various work programs covering infrastructure development, public services, and economic empowerment funded through the village budget. However, the monitoring and budget management processes are still carried out semi-manually, resulting in reporting delays, limited transparency, and suboptimal allocation of funds based on actual activity needs. This study aims to design and develop a web-based work program monitoring information system integrated with the Activity Based Budgeting (ABB) method. The research method used is Research and Development (R&D), while the system development applies the Waterfall model consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The implementation of the ABB method enables budget allocation based on activities, allowing each cost component to be traced in a more detailed and measurable manner. The system was developed using the PHP programming language and MySQL database, featuring program management, activity and resource recording, budget realization monitoring, comparative reports of budget and realization, and a public dashboard. The implementation results indicate that the system is able to automatically and in real-time detect budget variances and accelerate the monitoring and reporting process by approximately 60% compared to the previous manual method. Functional testing using Black Box Testing shows a validity level of 100% across all test scenarios. Therefore, the developed system is not only technically feasible but also effective in improving efficiency, transparency, and accountability in managing village work programs and budgets.